Oportunidades y riesgos de inversión en la industria del cannabis en Colombia 2023 (2024)
Colombia is emerging as a key player in the emerging global cannabis market. The country has great potential to become a leader in the production and export of cannabis products thanks to its favorable climatic conditions and a regulatory framework that is increasingly promising. The recent approval of laws that encourage investment in the sector has generated notable interest from national and foreign investors. The Colombian cannabis market offers a wide range of opportunities. The growing demand for cannabis-based products, both nationally and internationally, has fueled the growth of this industry. Despite the dynamic nature of the legal framework, it provides a relatively stable environment for companies operating in the sector.